Peran Mediasi pada Lembaga Alternatif Penyelesaian Sengketa Perbankan Indonesia (LAPSPI) - Muslih, Muslih (Ecobankers : Journal of Economy and Banking, 2021)
Mediation is one of the most effective dispute resolution alternatives for the parties to the dispute, especially for financial service actors with consumers. This forum is widely used in business dispute resolution because it can provide the existence and continuation of business relationships. Therefore the national banking sector association established an alternative dispute resolution institution outside the court that specifically handles complaints and dispute resolution in the banking sector (LAPSPI), on the basis of the Financial Services Authority Regulation (POJK) Number. 1/ POJK.07 / 2013 concern Protection of Financial Services Sector Consumers and Regulation Number. 1 / POJK.07 / 2014, concern Alternative Institutions for Settlement of Disputes in the Financial Services Sector. Of the various options for dispute resolution services such as Mediation, Adjudication and Arbitration, Mediation services are the main choice for parties to settle their disputes. Abstrak Mediasi merupakan salah satu alternatif penyelesaian sengketa yang sangat efektif bagi para pihak yang bersengketa, terlebih bagi para pelaku jasa keuangan dengan konsumennya. Forum ini banyak dipakai dalam penyelesaian sengketa bisnis karena dapat memberikan eksistensi dan kelanjutan hubungan bisnis. Oleh karenanya asosiasi sektor perbankan nasional membentuk suatu lembaga alternatif penyelesaian sengketa di luar peradilan yang secara khusus menangani pengaduan dan penyelesaian sengketa di sektor perbankan (LAPSPI), dengan dasar Peraturan Otoritas Jasa Keuangan (POJK) Nomor. 1/POJK.07/2013 tentang Perlindungan Konsumen Sektor Jasa Keuangan dan Peraturan Nomor. 1/POJK.07/2014 tentang Lembaga Alternatif Penyelesaian Sengketa di Sektor Jasa Keuangan. Dari sekian pilihan layanan penyelesaian sengketa seperti Mediasi, Adjudikasi dan Arbitrase, layanan Mediasi menjadi pilihan utama bagi para pihak dalam menyelesaikan sengketanya.